Cardiac biomarkers and COVID-19: A systematic review and meta-analysis - Wen An; Ju-Seop Kang; Qiuyang Wang; Tae-Eun Kim (Elsevier, 2021)
Objective: To systematically investigate the relationship between cardiac biomarkers and COVID-19 severity and mortality. Methods: We performed a literature search using PubMed, Web of Science, and Google Scholar. The standardized mean difference (SMD) and 95% confidence interval (CI) were applied to estimate the combined results of 67 studies. A meta-analysis of cardiac biomarkers was used to evaluate disease mortality and severity in COVID-19 patients. Results: A meta-analysis of 7812 patients revealed that patients with high levels of cardiac troponin I (SMD = 0.81 U/L, 95% CI = 0.14-1.48, P = 0.017), cardiac troponin T (SMD = 0.78 U/L, 95% CI = 0.07-1.49, P = 0.032), high-sensitive cardiac troponin I (SMD = 0.66 pg/mL, 95% CI = 0.51-0.81, P < 0.001), high-sensitive cardiac troponin T (SMD = 0.93 U/L, 95% CI = 0.21-1.65, P = 0.012), creatine kinase-MB (SMD = 0.54 U/L, 95% CI = 0.39−0.69, P < 0.001), and myoglobin (SMD = 0.80 U/L, 95% CI = 0.57-1.03, P < 0.001) were associated with prominent disease severity in COVID-19 infection. Moreover, 9532 patients with a higher serum level of cardiac troponin I (SMD = 0.51 U/L, 95% CI = 0.37-0.64, P < 0.001), high-sensitive cardiac troponin (SMD = 0.51 ng/L, 95% CI = 0.29-0.73, P < 0.001), high-sensitive cardiac troponin I (SMD = 0.51 pg/mL, 95% CI = 0.38-0.63, P < 0.001), high-sensitive cardiac troponin T (SMD = 0.85 U/L, 95% CI = 0.63-1.07, P < 0.001), creatine kinase-MB (SMD = 0.48 U/L, 95% CI = 0.32-0.65, P < 0.001), and myoglobin (SMD = 0.55 U/L, 95% CI = 0.45−0.65, P < 0.001) exhibited a prominent level of mortality from COVID-19 infection. Conclusion: Cardiac biomarkers (cardiac troponin I, cardiac troponin T, high-sensitive cardiac troponin, high-sensitive cardiac troponin I, high-sensitive cardiac troponin T, creatine kinase-MB, and myoglobin) should be more frequently applied in identifying high-risk COVID-19 patients so that timely treatment can be implemented to reduce severity and mortality in COVID-19 patients.